Calcineurin inhibitors revisited: A new paradigm for COVID-19? - Hage, René (Braz J Infect Dis, 2020)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) can cause mild, moderate or severe disease (COVID-19). In severe disease, there is hyperinflammation causing severe symptoms. Severe COVID-19 is an immunological phenomenon, rather than a direct viral damage disease. Therapies for COVID-19 are all investigational therapies. In case of severe disease, treatment with a calcineurin inhibitor could be promising. In this article we explain the mechanisms of calcineurin inhibitor treatment for COVID-19, based on experiences seen in solid organ transplant recipients who suffered from COVID-19.